Effect of CO2 Flow Rate on the Pinang Frond-Based Activated Carbon for Methylene Blue Removal - S. G. Herawan; M. A. Ahmad; A. Putra; A. A. Yusof (The Scientific World Journal)
Activated carbons are regularly used the treatment of dye wastewater. They can be produced from various organics materials having high level of carbon content. In this study, a novel Pinang frond activated carbon (PFAC) was produced at various CO2 flow rates in the range of 150–600 mL/min at activation temperature of 800°C for 3 hours. The optimum PFAC sample is found on CO2 flow rate of 300 mL/min which gives the highest BET surface area and pore volume of 958 m2/g and 0.5469 mL/g, respectively. This sample shows well-developed pore structure with high fixed carbon content of 79.74%. The removal of methylene blue (MB) by 95.8% for initial MB concentration of 50 mg/L and 72.6% for 500 mg/L is achieved via this sample. The PFAC is thus identified to be a suitable adsorbent for removing MB from aqueous solution.